Enacting strategies for graduate employability : how universities can best support students to develop generic skills : final report : appendices (part B). - Bennett, Dawn (Office for Learning and Teaching, 2016)
Appendices from the final report of a project that responded to growing social and economic demands for higher education graduates who can negotiate rapidly transforming employment contexts. The project was based on the premise that higher education institutions have responsibility for helping students gain the skills, knowledge and personal attributes required of them in the initial stages of their careers. The project emerged from the understanding that despite evidence on what is required by employers, the existence of graduate attributes statements, and a large body of scholarly literature, many graduates are not optimally work ready (Fullan & Scott, 2014). The appendices include measurement instruments, case studies and an evaluation.